Variation in follicle health and development in cultured cryopreserved ovarian cortical tissue: a study of ovarian tissue from patients undergoing fertility preservation. (27th May 2021) - Walker, Charlotte A.; Bjarkadottir, Briet D.; Fatum, Muhammad; Lane, Sheila; Williams, Suzannah A.
Abstract: This study investigated how follicle health and development in human ovarian tissue cryopreserved for fertility preservation varied between patients before and after 6 d of in vitro culture. Ovarian tissue from 12 patients (9–25 years) was used. In 3 patients, a 1hr neutral red (NR) incubation was used to identify tissues with viable follicles. Tissues were fixed, sectioned and follicles staged and graded for health. Inter-patient differences were observed in the non-cultured tissue in the number of both healthy follicles ( p = 0.005) and growing follicles ( p = 0.005). After culture there was significant variation in the number of transitional, primary and secondary follicles between patients ( p < 0.001). Asymmetric primary follicles with a single complete layer of granulosa cells plus two or more additional partial layers were 5.5 times more likely to be observed in cultured compared to non-cultured tissue ( p = 0.0063). Non-cultured ( p = 0.0125) and cultured ( p < 0.001) tissue selected using NR had more healthy follicles compared to tissue not selected using NR. Non-cultured and cultured tissue selected using NR had more healthy follicles compared to tissue not selected using NR ( p = 0.0125; p < 0.001). We demonstrate that inter-patient variation exists in the health and development of follicles before and after culture. Culture systems need to be optimized to support cryopreserved ovarian tissue and these findings should prompt researchers to consider patient variation when evaluating culture systems.